Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae) - Murdy, Edward O.; Shibukawa, Koichi (Zootaxa, 2003)
A new species of amblyopine goby, Odontamblyopus rebecca, is described on the basis of 37 specimens from Vietnam. It differs from other species of Odontamblyopus by the following combination of characters: caudal vertebrae typically 20; dorsal fin with 44-48 total elements; anal fin with 37-42 total elements; and pectoral-fin ray count 40-51. This species is figured and compared with other known species of Odontamblyopus.